Ortotropna elastičnost lesa - Torelli, Niko (Les (Ljubljana), 2002)
In wood the elastic deformation occurs by bond stretching and distortion of polymeric constituents. The elastic strain is for the most part the major component of the total strain, even at very long times. For practical purposes the time dependent deformation may be neglected. Accordingly the wood can be treated to a first approximation as a linear elastic material. The compliance and stiffness matrices are presented and related to the engineering form of Hooke's law. Values of elastic constants for wood and some important isotropic materials are presented. The differences among the elastic constants of wood are related to the anisotropy of wood structure.
Keywords: les; anizotropija; elastičnost